INTERAKSI DAN KEPENTINGAN ELIT PADA PERUBAHAN STATUS RUMAH SAKIT DAERAH MENJADI PERSEROAN TERBATAS - Ayuningtyas, Dumilah (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2011)
The Provincial Administration of Jakarta turned Pasar Rebo Hospital, Cengkareng Hospital and Haji Hospital into limited liabilities corporations through the issuance of Provincial Regulation No. 13, 14, 15 in 2004. To identify the interaction between elite and their role toward public hospital privatization. This study examines the factors underlying the establishment of the privatization policy, and the interaction between elites and their role toward public hospital privatization. This study found that the interaction between elites, both political elites and non political elites, was influenced by their interest, ideology and behavior. From these cases of hospital privatization, it can be analyzed that all elites that involved in this process have their own interests, whether it be the desire to defend the power and ownership, vision and purpose, a belief in values, including the history of the establishment or the financial aspect. In the case of privatization of government hospitals in Jakarta, elites’ personality – including the commitment preferences and values or vision- proven to influence the process of formulation, implementation, and termination of the policy. Policy and politics in health sector has to be directed to make sure that state is not only become the arena of vested interest and social politics conflict. The role of the state as regulator and policy maker must delivered fairly and proportionally to guarantee the public health interest become the major priority rather than profit orientation, include the role and involvement private sector and other ruling elite.